Formas crediticias en la Maragatería: obligaciones y censos en los siglos XVII y XVIII (Estudios humanísticos. Geografía, historia y arte, 1988)
Taxes and mortgages were the most popular credit formulae all throughout the Modern Age in the province of LEON. Although they share a common aim, there are important differences between them, both as to the dynamics and function which extend loans. Besides, taxes enjoyed a wide success, aboye all in the l8th. century.These formulae through which peasants ran finto debt gave birth to new relationships of dependence in society. The group of creditors is made up by the clergy, the industrial bourgeoisie and the aristocracy.On the other hand, loans did not help to introduce improvements in structures and techniques -but they contributed to the keeping up of a subsistence level of production and to produce a bigger income to privileged classes